The correlation between vitamin D and autoimmune thyroid function – short review - Piekarska, Małgorzata; Marcela Maksymowicz,; Radosław Kasperski,; Agata Pikulicka,; Katarzyna Pacek, (Journal of Education, Health and Sport, 2021)
Vitamin D is traditionally associated with the regulation of mineral metabolism and bone homeostasis, and its deficiency is the cause of diseases such as osteoporosis or osteomalacia. However, numerous studies in recent years suggest that thanks to the common expression of the vitamin D receptor (VDR) on the cells of the body and the related additional anti-inflammatory, immunomodulating, antioxidant, anti-fibrotic vitamin D effects, it may play a role in the development and progress of autoimmune diseases and tumors. The collected data suggest that low vitamin D levels correlate with the occurrence of autoimmune diseases of the thyroid gland and that there is a significant correlation between 25(OH)D and anti-TPO or anti-Tg levels. However, these data are inconclusive and further research is needed to confirm this relationship and determine whether lowered vitamin D titer is the cause or rather the consequence of autoimmune thyroid disorders, and whether vitamin D supplementation could prove to be an effective prophylaxis and treatment.